Hydrochemical response acid mine drainage to the storm event and metal loading in ex-mamut coppermine - Feona Isidore (2015)
The purpose of this study is to determine the dissolved metal status during low flow and its behaviour during the storm event. This study also estimates the dissolved metal removal and Metal loading from the Mamut ex-coppermine. Continuous water discharge measurement was recorded from March 2010 to March 2011 while water samples were taken from July 2010 until June 2012 using water level sensor and data logger. Water samples and discharge measurement was taken in seven sampling stations. Surface water samples were collected manually once a month and more regularly during storm event. Storm event samples were collected in December 2012. Six elements (Cu, Al, Fe, Mn, Zn, SO4) were analysed for the water samples using ICP-OES and Sulfaver 4 method (Hach). The water results for dissolved metals were then used in metal loading analysis in Mamut coppermine. Mass balance method was used to estimate the removal of metals in the temporary settling pond (TSP) from dilution process. The average concentration of sulphate in Mamut is 676.5 mg/L. The trends of dissolved metals during lowflow in Mamut is as follows Al > Fe > Cu > Mn > Zn and there are three hysteresis pattern had been identified during the storm event. The removal of metals in TSP spillway is Fe (86%), Cu (39%), Al (32%), Zn (6%), Mn (2.5%). This is an indication that different behaviour of dissolved metals observed to tolerate dilution process. The metal loadings estimated for the discharge from mine pit (Station M6) are Fe (364.2 - 555.6 kg/day), Al (1209 - 1453.8 kg/day), Cu (142.8 - 231.6 kg/day), Zn (76.13 - 86.54 kg/day), Mn (350.4 - 459.8 kg/day). Loads of dissolved metal reduced substantially in Station M7 due to the dilution and metal attenuation.